Uncovering The Potential of Low Resistivity Reservoirs Through Integrated Analysis: A Case Study from The Talang Akar Formation in The South Sumatra Basin - Fiqya Fairuz Zaemi; Rian Cahya Rohmana; Widi Atmoko (Scientific Contributions Oil and Gas, 2022)
The study area is an oil and gas field that has a low resistivity reservoir zone in the Talang AkarFormation, South Sumatera Basin. The reservoir zone is composed of siltstone and sandstone that was depositedin a shallow to transitional marine environment. The aim of this study is to identify and determine the potential oflow resistivity reservoirs in the study formation. The data used in the study include well log, mud log, core data(porosity, permeability, petrography), formation water analysis, and biostratigraphy. The methodology includesqualitative analysis to determine reservoir potential zones (quick look interpretation) and the reason for low resistivityreservoirs, as well as quantitative analysis to calculate petrophysical parameters. The results of the quicklook analysis showed 77 low resistivity reservoir zones, but the petrophysical analysis identified 25 low resistivityreservoir zones as potential candidates for drill steam test (DST). Factors causing low resistivity reservoirs inthe study area include clay mineral content (kaolinite and illite), conductive minerals (pyrite and siderite), highsalinity formation water (>10,000 ppm), very fine to medium sand grain size (0.063 - 0.5 mm) distribution ofclay minerals (laminated and dispersed clay), and thin laminates. The results of the petrophysical analysis showthat shale volume is less than 30%, porosity is greater than 14%, permeability is greater than 10 mD, and watersaturation is less than 70%.